The Impact of Beetroot Juice Supplementation on Hemoglobin Levels in Patients Diagnosed with Anemia - Sakar Emad Ali; AL-Qadhi, Israa Yahia (Universitas Muhammadiyah Sidoarjo, 2025)
Anemia is a widespread health problem caused by nutritional deficiencies or chronic diseases, often leading to reduced hemoglobin levels and serious complications if untreated. Beetroot (Beta vulgaris L.) is traditionally used as a dietary supplement due to its high iron, folate, and antioxidant content, which may improve hemoglobin synthesis. Although beetroot juice is consumed for its nutritional benefits, limited clinical evidence exists regarding its effect on hemoglobin levels in anemic and pregnant women in Iraq. This study aimed to evaluate the impact of beetroot juice supplementation on hemoglobin concentration in anemic patients, including pregnant women. Results: A total of 25 anemic participants (15 non-pregnant and 10 pregnant women) were enrolled and received beetroot juice twice daily for four weeks. In non-pregnant anemic patients, hemoglobin levels significantly increased from 10.29 ± 0.25 g/dL to 11.19 ± 0.21 g/dL (p = 0.0297). In pregnant women, hemoglobin levels rose from 9.56 ± 0.26 g/dL to 10.23 ± 0.27 g/dL, though the change was not statistically significant (p = 0.0855). This study provides one of the first structured evaluations in Iraq demonstrating beetroot juice as a natural dietary supplement capable of significantly improving hemoglobin levels in non-pregnant anemic patients. The findings suggest that beetroot juice may serve as a safe, accessible, and effective nutritional intervention for managing anemia, though further large-scale studies are recommended, particularly for pregnant women. Highlights: Beetroot juice supplementation significantly increased hemoglobin levels in non-pregnant anemic patients (p = 0.0297). Pregnant women showed a non-significant rise in hemoglobin after beetroot juice intake (p = 0.0855). Beetroot juice represents a safe, accessible, and natural nutritional intervention for anemia management